Sentence Context Differentially Modulates Contributions of Fundamental Frequency Contours to Word Recognition in Chinese-Speaking Children With and Without Dyslexia - Zhang, Linjun; Li, Yu; Zhou, Hong; Zhang, Yang; Shu, Hua (Frontiers in Psychology, 2020)
Previous work has shown that children with dyslexia are impaired in speech recognition in adverse listening conditions. Our study further examined how semantic context and fundamental frequency (F0) contours contribute to word recognition against interfering speech in dyslexic and non-dyslexic children. Thirty-two children with dyslexia and 35 chronological-age-matched control children were tested on the recognition of words in normal sentences versus wordlist sentences with natural versus flat F0 contours against single-talker interference. The dyslexic children had overall poorer recognition performance than non-dyslexic children. Furthermore, semantic context differentially modulated the effect of F0 contours on the recognition performances of the two groups. Specifically, compared with flat F0 contours, natural F0 contours increased the recognition accuracy of dyslexic children less than non-dyslexic children in the wordlist condition. By contrast, natural F0 contours increased the recognition accuracy of both groups to a similar extent in the sentence condition. These results indicate that access to semantic context improves the effect of natural F0 contours on word recognition in adverse listening conditions by dyslexic children who are more impaired in the use of natural F0 contours during isolated and unrelated word recognition. Our findings have practical implications for communication with dyslexic children when listening conditions are unfavorable.